Vocational counselling of students with special educational needs from the viewpoint of principals of mainstream schools - Baranauskienė, Ingrida; Jankutė, Milda (Social Welfare: Interdisciplinary Approach, 2012)
It is especially important to appropriately prepare students with special educational needs for labour activity. The integration of these students in vocational life is possible only through the improvement of labour education and vocational counselling. The article analyzes vocational counselling of students with special educational needs from the viewpoint of principals of mainstream schools. Their viewpoint towards vocational counselling for persons with special educational needs has been revealed; it has been analyzed how vocational counselling for students with special educational needs is provided in mainstream schools; the principals’ infl uence on vocational counselling of students with special educational needs has been investigated.
Keywords: mainstream school; principal of mainstream school; students with special educational needs; vocational counselling